The role of evidence according to the International Standard on Auditing (ISA 500) in improving audit quality A Survey Study of the Opinions of a Sample of Certified Public Accountants and Auditors in Erbil - Azwar Anwar Othman; Arshad Sedeeq Abdullah; Halmat Faqe Hussein (Zanco Journal of Human Sciences, 2025)
This research aims to clarify the importance of the International Standard on Auditing (ISA 500) in improving audit quality by enhancing confidence in the auditor's report. Obtaining sufficient and appropriate evidence is a fundamental factor for the confidence of users of financial reports in the auditor's opinion. To achieve this, the research relied on the city of Erbil, where the number of participants reached (91) individuals. The research also used descriptive statistical methods, variable analysis, and hypothesis testing using the (SPSS) program. The research reached a set of conclusions, the most important of which is that the International Standard on Auditing (ISA 500) plays a pivotal role in ensuring that auditors can collect reliable, sufficient, appropriate, and objective evidence to support the audit results. By adhering to this standard, the quality of auditing can be significantly improved, leading to increased confidence in the reports submitted by the auditor. Based on this the International Auditing Standard (ISA 500) and adhering to its paragraphs, in addition to the evidence of proof, by all auditing companies and accounting control offices in the city of Erbil, in order to improve professional performance in the auditing process and continuous improvement in the final reports submitted by the auditor so that they are of high quality and facilitate users of the reports.